Optimum distribution of thermal insulation material for constant insulation material volume or a given investment cost - Demir, Hakan; Sevindir, M. Kemal; Agra, Ozden; Atayilmaz, S. Ozgur; Teke, Ismail (AMER INST PHYSICS, 2015)
Most of the recent studies based on the alternative energy sources and efficient use of energy due to the rapidly exhausting fossil energy sources. Insulation is one of the solutions applied to decrease heat losses or gains. Present studies require tedious iterations to achieve a solution for optimum distribution of thermal insulation material for the volumes confined with environments at different temperatures such as cold storages. In this study, a general analytical solution for the optimum distribution of thermal insulation material is given for the volumes confined with environments at different temperatures for a given investment cost or constant insulation material volume. Analytical solution technique given in this study eliminates the need for tedious iterations or using a specialized computer software, and can also be combined with economic analysis models to include effects of economical parameters such as fuel price, interest rate, etc. A case study is also given for explanation and application of suggested methodology for a room confined with environments at different temperatures. It is shown that optimum distribution of insulation material easily achieved by one step analytical solution technique. (C) 2015 AIP Publishing LLC.
Keywords: BUILDING WALLS; EXTERNAL WALLS; THICKNESS; OPTIMIZATION; MODEL; ORIENTATIONS; PERFORMANCE; Science & Technology - Other Topics; Energy & Fuels